Model Technopreneurship Berbasis Explainable Artificial Intelligence (Xai) untuk Meningkatkan Kepercayaan dan Intensi Adopsi Teknologi pada Startup Digital - Nurhayati, Sri; Eddy Soeryanto Soegoto; Tri Utomo Wiganarto (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2026)
This study aims to develop a technopreneurship model based on Explainable Artificial Intelligence (XAI) to enhance trust and technology adoption intention in digital startups. The main problem in the implementation of Artificial Intelligence (AI) is the low level of user trust caused by the black-box nature of AI systems, which makes it difficult for users to understand the decision-making process generated by the technology. This study uses a quantitative approach with the Partial Least Squares-based Structural Equation Modeling (SEM-PLS) method involving 100 respondents consisting of students and digital startup actors. The variables used in this study include explainability and transparency as independent variables, trust as a mediating variable, and adoption intention as the dependent variable. The results show that explainability and transparency have a positive and significant effect on trust, and trust has a significant effect on adoption intention. In addition, trust is proven to act as a mediating variable that connects XAI characteristics with technology adoption. The findings also indicate that explainability has a stronger influence than transparency in building user trust. This study provides theoretical contributions by integrating the concept of XAI into the technopreneurship model, as well as practical contributions for digital startups in developing more transparent, understandable, and trustworthy AI systems to increase technology adoption.